(3cJGH aj GdMOjKs - (3GdefGhj, CHh RcQjG, TQa GdOjf, jMji Hf eMeO Hf eMeO, J (B871 (3g`s
(3ChdgG (B:s
(3bhd GdTGQM aeG abO ajg TQW ef TQhW GdbHhd(B. (3bSe Cj hJMJg CbSGe (B...s
(3BNQgG (B:s
(3heLghd hTPhP hYdI bGOMI(B... (3hgh SGbW CjVG hdG JCNP GdNGeS YTQ(B...(3hgh SGbW CjVG SGOS KdGKjgG eG ajg VYjas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B167s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs